2006
DOI: 10.1007/s10840-006-9031-7
|View full text |Cite
|
Sign up to set email alerts
|

Posterior left atrial–esophageal relationship throughout the cardiac cycle

Abstract: Under normal conditions, there is little change in the anatomical relationship between the posterior left atrium and the esophagus during the entire cardiac cycle. However, due to the interpatient variability at the esophageal location, identification of esophageal location may help prevent complications during catheter ablation procedures involving the left atrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Sra et al. have shown that the esophagus is in contact with the posterior left atrium throughout the cardiac cycle but may run toward either the left or right pulmonary veins. In every case of our study, the esophageal position allowed study of the left atrium with no patient excluded due to the course of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sra et al. have shown that the esophagus is in contact with the posterior left atrium throughout the cardiac cycle but may run toward either the left or right pulmonary veins. In every case of our study, the esophageal position allowed study of the left atrium with no patient excluded due to the course of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that the heart can be paced through the esophagus in emergencies and all ablating electrophysiologists are aware of the dangers of esophageal trauma with left atrial ablation. Computed tomography (CT) studies have shown that the esophagus is in contact with the left atrium throughout the cardiac cycle . It may run a course closer to the right or left pulmonary veins, but it always contacts the posterior left atrium.…”
Section: Rationale For the Studymentioning
confidence: 99%
“…Unfortunately, since the esophagus is a mobile organ, the preoperative esophageal location may not accurately reflect its location at the time of ablation. Although short-term esophageal motion during the cardiac cycle does not seem to be critical, 21 a series of studies have reported conflicting results on the magnitude of esophageal position change across serial imaging studies, with some suggesting minimal motion, 22,23 and others reporting large position changes and concluding to the inefficacy of a personalization strategy based on prior imaging. 10,24,25 None of these prior studies have assessed the actual LA-esophagus distance, but rather the projection of the entire course of the esophagus on the LA.…”
Section: Use Of Preoperative Imaging To Prevent Esophageal Injurymentioning
confidence: 99%
“…The esophageal mucus with its intrinsic clearance acts as conductive electrolyte. Due to the close proximity to the heart [9], esophageal electrodes sense both atrial as well as ventricular electrical signals with high quality [10].…”
Section: Introductionmentioning
confidence: 99%